Multi-Agent Simulation in the Inter-Organizational Trust Model and Knowledge Sharing in the Automotive Industry - Afrin Fauzya Rizana; Fadillah Ramadhan (Jurnal Teknik Industri, 2019)
Two organizations can share knowledge to determine the success of their collaboration. Effectiveness in knowledge sharing affects organizational performance and trust between organizations. This study aims to identify the implementation of multi-agent simulations to increase trust in sharing knowledge between organizations. A multi-agent simulation approach was used in this study. The research model was adopted from previous research.  Several hypotheses and path coefficients were tested in simulation models. This study showed that multi-agent simulation is suitable as a problem-solving method for complex issues such as knowledge sharing.  In addition, this study identified individual factors such as likability and expertise in the success of knowledge sharing between organizations.